Clinical outcome on cardiovascular responses with different exercise characteristics in hypertensive patients / Noor Fatihah Ilias - Ilias, Noor Fatihah (2017)
Presently, exercise training has been recommended as a useful treatment for management hypertension. It has been speculate, different exercise intensities may results different effect on hypertension. The purpose of the present study was to address the effect of different exercise intensities and optimal exercise volume on cardiovascular responses in management hypertensive patients. A systematic review and meta-analysis was conducted using MEDLINE search (1985 to April 30th, 2016), eighteen studies were included, involving 22 intervention groups; 9 (41%) were moderate intensity, 13 (59%) were vigorous/high intensity, providing a total of 655 were exercise and 352 were control, totaling 1017 hypertensive patients. Results were analyzed using Revman version 5.3 software. Result suggests that possibly vigorous/high intensity and higher energy expenditure may elicit greater improvement in cardiovascular responses in management hypertensive patients. This meta-analysis found vigorous/high exercise intensity is more effective, therefore, a randomized controlled trial was conducted to compare between high intensity interval training (HUT) and moderate intensity continuous training (MICT) in management hypertensive patients. A total 9 patients (age = 40.29 ± 5.61; weight = 79.80 ± 11.7; height = 159.14 ± 4.74; year of hypertension = 4.14 ± 2.80) were randomly assigned into HUT (n = 4) at > 85% heart rate reserved (HRR) and MICT (n = 5) at 40% to 60% HRR. A mix between-within ANOVA was used to analyze the changes blood pressure between groups. Study found blood pressure response was greater after HUT than MICT. Possibly HUT is superior in management of hypertensive patients.